Types of Carbon Dioxide Reactions and Current Advances - Xu, Zihan (International Journal of Natural Resources and Environmental Studies, 2026)
Carbon dioxide (CO2) conversion has attracted increasing attention as a promising strategy for both carbon mitigation and the production of value-added chemicals. However, the high thermodynamic stability and kinetic inertness of CO2 make its efficient transformation challenging. In this review, CO2 conversion is classified according to whether the oxidation state of the central carbon atom changes during the reaction process, dividing it into reductive and non-reductive pathways. Reductive conversion mainly produces CO, CH4, and multicarbon (C2+) products, while non-reductive conversion mainly yields carbonates, carbamates, and urea derivatives through direct functionalization. The characteristics, representative pathways, and major challenges of these product systems are briefly discussed. Overall, reductive pathways are more suitable for fuel production and carbon upgrading, whereas non-reductive pathways show advantages in the selective synthesis of fine chemicals. This review provides a concise framework for understanding CO2 conversion routes and highlights key challenges and future directions for their sustainable development.